Alternative string theory in twistor space for N = 4 super-yang-mills theory - Berkovits, Nathan [UNESP] (American Physical Society (APS), 2004)
An alternative string theory in twistor space was proposed in order to describe the perturbative N=4 super-Yang-Mills theory. It was shown that the simple form of maximal helicity violating (MHV) amplitudes of the theory had a natural generalization to the nonmaximal helicity violating amplitudes. The sting theory was shown to use twistor worldsheet variable, which manifested spacetime superconformal invariance. It was also shown that the tree-level super-Yang-Mills amplitudes, in the theory, comes from open string tree amplitudes, as opposed to coming from D-instanton contributions.